Implementasi Sifat – Sifat Nabi Muhammad dalam Kepemimpinan pendidikan di Masa Modern - Nurul Hidayah , Maulida; kasdar, Moh. Khusnul Abid (Universitas Muhammadiyah Prof Dr Hamka, 2024)
This study aims to examine and learn about the characteristics of the educational leadership of the Prophet Muhammad in modern times. The research method used is a literature study using data sources from the book Educational Leadership and several journals, articles, and national and international seminar proceedings. The results of this study indicate that the educational leadership carried out by the Prophet Muhammad can provide an example to other leaders on how to be a good leader. In addition to having good morals, the Prophet Muhammad also has four mandatory characteristics that are the basis for the criteria for a good leader: siddiq, amanah, tabligh, and fathanah. Thus, it is appropriate for a leader to emulate the characteristics of the Prophet Muhammad in carrying out his leadership. He is an ideal leader and a good role model for his people.